2022
DOI: 10.21037/tcr-21-2841
|View full text |Cite
|
Sign up to set email alerts
|

Thematic trends and knowledge structure map of sentinel lymph node biopsy for breast cancer: a bibliometric analysis from 2010 to 2019

Abstract: Background: Breast cancer is the leading cancer-related deaths among women. Although great progress has been made in clinical surgical treatment, it is still urgently needed to look for a treatment model with smaller wounds, lower damage, and a better prognosis. Sentinel lymph node biopsy (SLNB) is a minimally invasive technique for breast cancer treatment, which can correctly assess the patients' condition, prognosis, and treatment response.Methods: We performed a PubMed-based bibliometric analysis to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In this regard, we are pleased to highlight the remarkable findings published by Huo et al [2022] (10), entitled "Thematic trends and knowledge structure map of sentinel lymph node biopsy for breast cancer: a bibliometric analysis from 2010 to 2019". They examined a total of 4,152 articles published in 624 journals, discovered that in the previous ten years, researchers were very interested mainly in SLNB and sought to determine its benefits and drawbacks.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, we are pleased to highlight the remarkable findings published by Huo et al [2022] (10), entitled "Thematic trends and knowledge structure map of sentinel lymph node biopsy for breast cancer: a bibliometric analysis from 2010 to 2019". They examined a total of 4,152 articles published in 624 journals, discovered that in the previous ten years, researchers were very interested mainly in SLNB and sought to determine its benefits and drawbacks.…”
mentioning
confidence: 99%
“…Huo et al [2022] ( 10 ) also demonstrated the wide range of benefits of SLNB, which justifies its current use in clinical practice. Notably, SLNB causes less damage to the nerves and lymphatic tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation